Labial frenectomy before debonding of orthodontic braces using diode laser: A case report - Rhoshan, B; Swathi, S; Kumar , Jithesh; Jacob, Steve Mathew; Coeur, Paventhan Jolie; Ragul, I (Indian Journal of Case Reports, 2025)
Midline diastema is a common adult esthetic concern often linked to high labial frenal attachment. Traditional frenectomy using scalpels may cause pain, bleeding, and delayed healing. Diode lasers offer a minimally invasive alternative with improved precision and patient comfort. This case report presents the orthodontic and laser-assisted management of a 24-year-old male with generalized spacing and a 4 mm maxillary midline diastema due to a papilla-penetrating frenum. Fixed orthodontic treatment using McLaughlin, Bennett, and Trevisi (MBT) appliances achieved space closure, followed by a diode laser frenectomy using a 980 nm laser. The procedure was bloodless and suture free and healing was uneventful. Stability was maintained with a bonded lingual retainer and a Hawley retainer. Laser-assisted frenectomy proved to be a safe, effective adjunct to orthodontics, aiding in long-term stability and patient satisfaction.